A study on clinical profile and management of lump in breast at tertiary rural hospital, Wardha, Maharashtra, India - Chandak, S. R.; Tabrez, Md. Omar (International Surgery Journal, 2017)
Background: Breast lumps diseases are one of the most common diseases in India which include congenital, traumatic, inflammatory, hormonal mastopathy, benign and malignant neoplastic conditions. Around 200,000 cases of breast diseases are diagnosed annually. In India, as there is no study of breast disease conducted separately in rural India hence studies are required to evaluate the incidence and prevalence of breast lump diseases so that interventions can be done to educate and guide people about the risk factors, importance of screening and management strategies. Methods: We have conducted our study on 50 cases of lump in breast with the objective to know their incidence, clinical, pathological and radiological features of various breast swellings and different investigative approach different treatment modalities and their outcome presenting in rural India. Results: The present study of lump in the breast was based on 50 cases admitted in AVBRH, Wardha, Maharashtra, India. During this period maximum patient were of benign breast lump as compared to malignant. All patients were females with age variation from 15 years to 55 years. Majority of patients had lumps varying from 2 months to more than 12 months. Conclusions: Most of the patients from benign lump were managed with excision of lump and all patient of malignant lump underwent mastectomy.